A new species of Tenuipalpoides (Acari: Tetranychidae) from Astragalus (Leguminoseae) in Iran - Mahdavi, Sayed Mosayeb; Asadi, Mahdieh; Latifi, Malihe (Zootaxa, 2017)
A new species of the genus Tenuipalpoides (Tetranychidae: Tenuipalpoidini), Tenuipalpoides iraniensis sp. nov. is described and illustrated based on females and deutonymphs collected from Astragalus spp. (Leguminoseae) in Southern Iran (Hormozgan Province). This is the fifth report of this genus for the world and the first report of the tribe Tenuipalpoidini from Iran. The deutonymph of this genus is described for the first time and a key to the species of Tenuipalpoidini of the world is also provided.